The perception of a revolution: Venezuela entering a “post-chavism” period? - Reichenbach, Benjamin (2017)
Two years after the death of Hugo Chavez rifts between the government of his successor, Nicolas Maduro (PSUV), and the grassroots of Chavez’ movement, so called ‘chavismo’, erupted evidently. The sharp rise of oil prices in the world market fiercely tightened the economically and socially tense situation of Venezuela’s rentier economy. Therefore, Maduro’s government faces the dilemma of implementing economic structural reforms with huge political costs or inevitably approaching a national bankruptcy. However, the current crisis goes far beyond the government Maduro and ‘chavismo’. The political elites of the Fourth Republic (1958-1999) share the responsibility to the country’s structural problems. A politically stable and economically sustainable future perspective can only be developed with ‘chavismo’, not against it.